Testing and strength prediction of eccentrically-loaded circular concrete-filled double steel tubular stub-columns. (November 2021) - Ci, Junchang; Ahmed, Mizan; Jia, Hong; Chen, Shicai; Zhou, Daxing; Hou, Liqun
Abstract: Circular concrete-filled double steel tubular (CFDST) column is a high-performance composite column that has significant potential to be used in the construction of high-rise composite structures. This paper presents experimental and strength computational investigations on CFDST short columns that are subjected to eccentric compression load. A total of sixteen CFDST stub columns, two concrete-filled steel tubular (CFST) columns, and two double-skin concrete-filled steel tubular (DCFST) columns were tested to investigate their structural performance. The test behavior of the CFDST column loaded eccentrically is discussed and compared against its CFST and DCFST counterparts. The test results show that the CFDST column has improved strength and ductility under eccentric loading when compared with other composite columns. The strengths of the CFDST stub columns in this study together with the test strengths from the literature were used to assess the strength predictions by Eurocode 4 and AISC 360–16. It was found that the current predictions generally underestimate or overestimate the strengths. A new reduction factor for predicting the ultimate strengths of CFDST short columns under eccentric compression is proposed based on the test results. By adopting the newly proposed reduction factor and design method, the design predictions are found to be improved that provide reasonable estimations for circular CFDST columns loaded eccentrically. Highlights: A series of tests on CFDST stub columns are carried out loaded either concentrically or eccentrically. Influences of loading eccentricity, steel tube thickness on the column ultimate strengths are investigated. The applicability of the codified design methods is investigated. Design rules are proposed to calculate the ultimate strengths of CFDST columns under eccentric loading.